Economic pros and cons of living in Germany - Kolesnyk, D. V. (ТДАТУ, 2020)
It should be noted that pros and cons of living in Germany can help you to decide if this country is right for you. As long as you can manage the living expenses and taxes, you will find enough money available to keep you comfortable while you get the opportunity to go exploring at your leisure.
Keywords: taxes in Germany; treaties to prevent double-taxing; food prices in Germany